(untitled) (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
The background to this research is the lack of student interest in physics, with various underlying factors. Starting from the unavailability of learning modules in schools to the absence of measuring instruments, which results in students having difficulty calculating measurement results using measuring instruments that have never been seen or used before. Therefore, it is important to develop valid and practical modules, one of which is by using technology in teaching and learning activities, which is one of the steps in increasing the effectiveness of learning, with the help of Augmented Reality using the Assemblr Edu application and focusing on measurement material in class X. This research is research and development (R&D) using the 4D model (Define, Design, Development, Dissemination). However, this research only reached development at the practicality stage. Based on the results of data analysis, validation from material, media and interpretation experts was found to be 94.5%, 83.3% and 91.6%, respectively, in the very valid category. And the practicality of the module by teacher and students was obtained at 98.6% and 86.4% in the very practical category.